Knowledge attitude and practice on dengue among university students - Amanah, Mohamad Afhzan; Abdullah, Hasmah; Abdul Ghafar, Noraini (International Journal Of Community Medicine And Public Health, 2018)
Background: Knowledge, awareness, and practice regarding dengue are important to be cultivated especially among the young generation. This study was commenced to assess the level of knowledge, attitude and practice of dengue fever among undergraduate health science students of University of Science Malaysia, beside to determine the relationship between knowledge regarding dengue and practice of dengue prevention. Methods: Cross sectional survey among 250 undergraduate students was conducted to assess the level of knowledge, attitude, and practice toward dengue using a standardized questionnaire. Data was analysed using SPSS through a few statistical analyses. Results: Majority of the students had moderate level of knowledge, attitude, and practice toward dengue fever. There was a significant, positive, weak correlation between knowledge and practice regarding dengue fever (p<0.05). Conclusions: Level of knowledge, attitude and practice regarding dengue fever among the students could be increased. Social media could be used as an important medium in delivering information on dengue especially among the youths. Effort must be put to translate the components of knowledge into good practice of dengue prevention.